A comparison of orthodontic treatment outcomes using the Objective Grading System (OGS) and the Peer Assessment Rating (PAR) index - Chalabi Orfan; Preston Charles Brian; Al-Jewair Thikriat S.; Tabbaa Sawsan (Sciendo, 2015)
The use of objective criteria is essential to uniformly quantify and measure the severity of malocclusions and the efficacy of different treatment modalities. The Peer Assessment Rating (PAR) index and, more recently, the American Board of Orthodontics Objective Grading System (OGS) were developed to fulfill this need.